Isolation, characterization and identification of yeast in pindang eggs as a starter for fermented chicken eggs - Pratama, Andry; Gumilar, Jajang; Putranto, Wendry S.; Rukayadi, Yaya (Agricultural Research Communication Centre, 2026)
Background: The yeast in pindang eggs is indigenous. Isolation, characterization and identification of yeast in boiled eggs were carried out to determine the genus of yeast. The yeast has the potential to be a starter for fermented chicken eggs. This study aims to determine the characteristics of the yeast genus that has been isolated from boiled eggs and to determine the genus and species of yeast that have the best ability as a starter based on pH, total yeast count and reducing sugar content in fermented chicken eggs. Methods: This study was carried out by isolating, identifying, characterizing the yeast in pindang eggs and then carrying out chicken eggs fermentation by adding yeast with the ability to ferment sugar in chicken eggs. Result: The results show that pindang eggs are thought to contain the genera Candida, Hyphopichia and Pichia. These three yeasts have the ability to ferment sugar, making them suitable as starters for fermented chicken eggs. Pichia kudriavzevii is the best starter for fermented chicken eggs, producing the lowest pH (5.830) and the lowest reducing sugar content (0.058%) with low total yeast count (4.7 × 104 CFU/mL).